Managerialism in the public sector : perspectives and prospects - Tomo, Andrea (Routledge-Giappichelli studies in business and management., 2018)
"This book offers fresh insights into the complex and often unclear context of public sector management, providing a new theoretical and practical approach to the analysis and interpretation of these issues. It is grounded in the awareness that the public sector has too often exhibited inefficiencies, despite expensive measures taken, from manifold perspectives such as economic, social, organizational, and institutional for example. It acknowledges the lack of behavioral, cultural, and context-oriented research in the field, thus renewing the debate and expanding the current understanding of which organizational features characterize modern public administrations, what factors influence the predominance of different models, with a special focus on the Italian setting. The book benefits from a wholly comprehensive innovative methodological approach. The findings offer key implications for theory, practice, and policy-making, contending the importance of holistic approaches to the debate and abandoning pre-constituted schemes to put forth the relevance of behavioral models. It offers a key message: contextual-specific and cultural factors influencing individual behaviors are important and should better influence policy-making processes, towards "glocalization" in order to improve quality"--